2012
DOI: 10.3103/s0735272712100056
|View full text |Cite|
|
Sign up to set email alerts
|

Algorithm for multiplying two octonions

Abstract: In this work a rationalized algorithm for Dirac numbers multiplication is presented. This algorithm has a low computational complexity feature and is well suited to FPGA implementation. The computation of two Dirac numbers product using the naïve method takes 256 real multiplications and 240 real additions, while the proposed algorithm can compute the same result in only 88 real multiplications and 256 real additions. During synthesis of the discussed algorithm we use the fact that Dirac numbers product may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The computation of a sedenion multiplication using the naive method requires 240 additions and 256 multiplications, while an algorithm which is given in [8] can compute the same result in only 298 additions and 122 multiplications, see [8] for details. Moreover, efficient algorithms for the multiplication of quaternions, octonions and trigintaduonions with reduced number of real multiplications is already exist in literature, see [33], [7] and [9], respectively.…”
Section: Sequences (Numbers) Notationmentioning
confidence: 99%
“…The computation of a sedenion multiplication using the naive method requires 240 additions and 256 multiplications, while an algorithm which is given in [8] can compute the same result in only 298 additions and 122 multiplications, see [8] for details. Moreover, efficient algorithms for the multiplication of quaternions, octonions and trigintaduonions with reduced number of real multiplications is already exist in literature, see [33], [7] and [9], respectively.…”
Section: Sequences (Numbers) Notationmentioning
confidence: 99%
“…At first, we rearrange the rows of the matrix in the following order {1, 2, 3, 7, 5, 9, 4, 8, 6, 10, 11,17,13,19,15,21,12,18,14,20,16,22,23,27,25,29,24,28,26,30, 31, 32}. Next, we rearrange the columns of obtained matrix in the same manner.…”
Section: Synthesis Of a Rationalized Algorithm For Computing Kaluza N...mentioning
confidence: 99%
“…Efficient algorithms for the multiplication of various hypercomplex numbers already exist [12,13,14,15,16,17,18,19,20,21,22,23,24]. No such algorithms for the multiplication of Kaluza numbers have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Sariyildiz et al (2011) analyzed forward and inverse kinematics problems for a 6DOF manipulator using three methods: quaternions algebra, exponential mapping method and dual quaternions. Cariow et al (2015) elaborated and implemented a method which improves the computational efficiency of dual quaternions operations. The obtained results indicated that dual quaternions provide a compact and computationally efficient solution.…”
Section: Introductionmentioning
confidence: 99%